Enhancing Solar Power Efficiency: Implementation of Smart Inverter EGS002 in Renewable Energy Systems - Bontoc, Noriel; Patangke, Simon (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2025)
This study aims to evaluate the implementation of the intelligent inverter EGS002 in solar power generation systems PLTS in Indonesia focusing on improving energy efficiency power quality and system reliability The background of this study is the need to overcome energy fluctuations generated by PLTS in Indonesia which are influenced by changes in weather and sunlight intensity The method used in this study involves testing the performance of the EGS002 inverter under operational conditions of PLTS in Indonesia including measuring power conversion efficiency and Total Harmonic Distortion THD The results show that the EGS002 inverter has a power conversion efficiency of 92 5 and a low THD of 4 which meets the power quality standards required for integration with the electricity grid In conclusion the intelligent inverter EGS002 can improve the performance of PLTS systems especially in tropical Indonesia and has great potential to support a more efficient and sustainable renewable energy transition < p>